Potensi Terapi Antibodi Bispesifik sebagai Pengobatan Antikanker: Tinjauan Literatur - Yurafi Kun Naviaghani; Muhammad Aziz Hidayat (Aesculapius Medical Journal, 2026)
Abstract Bispecific antibodies are engineered antibodies capable of recognizing two targets simultaneously, thereby redirecting immune effector cells toward tumor cells or inhibiting two molecular pathways involved in cancer growth and therapeutic resistance. This literature review aimed to evaluate the mechanisms of action, efficacy, safety, and developmental challenges of bispecific antibodies in cancer treatment based on publications from 2020 to 2025. A literature search was conducted through Google Scholar using the phrase bispecific antibodies cancer therapy. Twenty articles were reviewed, comprising 17 primary studies and three review articles used as supporting sources. The investigated agents mainly acted through T-cell or natural killer-cell redirection, simultaneous blockade of two signaling pathways, and modulation of the tumor microenvironment. The strongest clinical evidence was identified for cadonilimab in cervical cancer, while zenocutuzumab demonstrated clinical activity in tumors harboring NRG1 fusions. Most other agents remained at the preclinical stage. Major challenges included cytokine release syndrome, immune-related toxicity, antigen heterogeneity, tumor resistance, and limited translation of preclinical efficacy into clinical benefit. Bispecific antibodies represent a promising therapeutic approach in oncology; however, their clinical implementation requires biomarker-guided patient selection, dose optimization, and comprehensive safety evaluation in adequately designed clinical trials. Keywords: bispecific antibodies, cancer, immunotherapy, targeted therapy.